Indicadores biológicos para avaliação do status de desenvolvimento em área de povoamento misto em Mata Atlântica após 12 anos de plantio - Déda, Rainan Matos (2017)
The Atlantic Forest, one of the planet’s most devastated and seriously endangered ecosystems since its colonization, was marked by the intensive land use, whether for the exploration of products, such as brazilwood, sugar cane, coffee, and cocoa, or for the use in livestock activities. As a consequence of its degradation history, this biome is highly fragmented, and many endemic species are considered to be endangered. Therefore, forest restoration has been an effective means of intervention that seeks to provide degraded ecosystems with the minimal conditions for the reestablishment of ecological processes. The increasingly development of works and techniques used to recover different ecosystems made necessary the establishment of indicators that allow periodic evaluations of recovery proposals and verify if the objectives have been accomplished. Natural regeneration is an indicator used to analyze the development status of areas undergoing ecological restoration. This indicator considers the entry of new individuals and species by means of seed rain, soil seed bank, and seedling bank. In addition, floristic surveys in these areas allow the evaluation of the success in the establishment of the planted species and the analyses of whether or not the dispersion mechanisms increased the number of species. This study was carried out aiming to know the natural regeneration process in a mixed settlement area in the Atlantic Forest, in the municipality of Laranjeiras, Sergipe, after 12 years of planting, and to identify the species composition of the local flora. The natural regeneration studies consisted of 30 fixed plots (20m x 30m). A soil sample (0.25 m x 0.25 m x 0.05 m) was collected from each plot to estimate the seed bank. For the seed rain evaluation, 1 m² wood collectors were used in the center of each plot. For the seedling bank, the diameter and height of shrub-arboreal individuals with circumference at soil height ≤ 15 cm were measured in 1 m² subplots in each plot. For floristic composition analysis, monthly collections were performed from August 2016 to June 2017 throughout the study area. In the seed rain, 10,070 seeds were collected, which were distributed in 37 species, with predominance of shrubarboreal individuals (50%) and zoocoric dispersion syndrome (46.67%). The seed bank presented a total of 12,322 seeds belonging to 53 species, being predominantly formed of herbaceous species (30.19%), mostly of the family Asteraceae. In the seedling bank, 169 individuals were sampled, being distributed in 24 species, with predominance of pioneer and initial secondary species. This fact suggests the area is at the initial succession stage. Genipa americana L., Schinus terebinthifolia Raddi., and Inga vera Willd were the regenerating species with the highest Importance Value (IV). Together, these three species accounted for about 70.05% IV. The floristic survey revealed the occurrence of 146 species distributed in 50 families, with greater representation of the families Fabaceae (26 spp.) and Asteraceae (16 spp.). Of the 34 species used at the initial reforestation planting, 27 were recorded in this study (79.41%), indicating that these species had a good establishment and have potential in the restoration of degraded areas located in the Atlantic Forest in the state of Sergipe.